2002
DOI: 10.1248/bpb.25.632
|View full text |Cite
|
Sign up to set email alerts
|

Paclitaxel Delivery Systems: The Use of Amino Acid Linkers in the Conjugation of Paclitaxel with Carboxymethyldextran to Create Prodrugs

Abstract: Paclitaxel (Taxol ® ), an anti-microtubule agent isolated from the trunk bark of the Pacific Yew tree, Taxus brevifolia, 1) shows great promise as an anti-neoplastic agent for a variety of human cancers including breast, ovarian, non small cell lung, head and neck cancers, leukemia, and melanoma. [2][3][4][5][6] Its unique mechanism of action is related to its ability to promote microtubule assembly and inhibit cell replication in the late G2 or M phases of the cell cycle.7) A major problem associated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(25 citation statements)
references
References 32 publications
1
24
0
Order By: Relevance
“…These experiments clearly demonstrate the higher stability of carbamate linkage over the ester bond (compounds 3 and 4) and also indicate that the modification of the more hindered C7 position lead to reduction of hydrolysis rate of the conjugates as also reported by other authors (Greenwald et al,350 1995; Sugahara et al, 2002). The stability was further improved with the introduction of PEG at both C2' and C7 positions.…”
Section: Water Solubilty and In Vitro Stability Of Peg-ptx Prodrugssupporting
confidence: 84%
“…These experiments clearly demonstrate the higher stability of carbamate linkage over the ester bond (compounds 3 and 4) and also indicate that the modification of the more hindered C7 position lead to reduction of hydrolysis rate of the conjugates as also reported by other authors (Greenwald et al,350 1995; Sugahara et al, 2002). The stability was further improved with the introduction of PEG at both C2' and C7 positions.…”
Section: Water Solubilty and In Vitro Stability Of Peg-ptx Prodrugssupporting
confidence: 84%
“…The amino acid linkages are relatively weak bonds; under certain conditions, the chemical bonds could break and release the drugs easily. 56 PEG as linker for the production of prodrugs has been widely investigated. 57,58 However, in vivo experiments have shown that a PEG drug system has lower efficacy than the drug alone.…”
Section: Discussionmentioning
confidence: 99%
“…9) We previously reported the necessity of controlled paclitaxel release to achieve antitumor effects in a colon26 carcinomabearing mouse model. 29) In that report, we discussed that the appropriate drug release rates from conjugates are essential to achieve antitumor effects. AZ10992 would be predicted to have more controlled drug release via the peptide linker as compared with the other paclitaxel dosage forms.…”
Section: Discussionmentioning
confidence: 99%